Tendency of Student Learning Style on the Achievement Level of Harsia Elementary School Students - Irwan Priyatna; Ngalimun Ngalimun (Peneliti.net, 2021)
This study aims to determine the difference in the level of learning achievement in terms of the learning style tendencies of SD Harsia North Bekasi students. This study uses a quantitative approach with a comparative method. The population in this study were students of SD Harsia. The research sample is all students in grades IV, V, and VI SD Harsia a total of 57 students taken by purposive sampling technique. The measuring instrument used in this research is a multiple choice questionnaire with a single answer for learning style variables, while the learning achievement level variable uses odd semester report cards documentation. The measuring instrument for learning style variables has been tested for validity using the reliability test with the Kuder-Richardson 21 (K-R 21) formula with the results of: 0.373 for aspects of visual learning style, auditory learning style of 0.468, and kinesthetic learning style of 0.429. The data analysis technique used is chi-square. The results showed that there was no difference in the level of learning achievement in terms of the learning style tendencies of SD Harsia North Bekasi students as evidenced by the chi-square value of 13.285 with p = 0.208 at the significance level (p <0.05). The implication of this research is that classroom teachers are advised to be able to design varied learning media and methods so that students are free to carry out activities, so that learning is faster and easier